Assessing whether early attention of very preterm infants can be improved by an omega-3 long-chain polyunsaturated fatty acid intervention: a follow-up of a randomised controlled trial. Issue 5 (26th May 2018) - Gould, Jacqueline F; Colombo, John; Collins, Carmel T; Makrides, Maria; Hewawasam, Erandi; Smithers, Lisa G
Abstract : Introduction: Docosahexaenoic acid (DHA) accumulates in the frontal lobes (responsible for higher-order cognitive skills) of the fetal brain during the last trimester of pregnancy. Infants born preterm miss some of this in utero provision of DHA, and have an increased risk of suboptimal neurodevelopment. It is thought that supplementing infants born preterm with DHA may improve developmental outcomes. The aim of this follow-up is to determine whether DHA supplementation in infants born preterm can improve areas of the brain associated with frontal lobe function, namely attention and distractibility. Methods and analysis: We will assess a subset of children from the N-3 (omega-3) Fatty Acids for Improvement in Respiratory Outcomes (N3RO) multicentre double-blind randomised controlled trial of DHA supplementation. Infants born <29 weeks' completed gestation were randomised to receive an enteral emulsion containing 60 mg/kg/day of DHA or a control emulsion from within the first 3 days of enteral feeding until 36 weeks' postmenstrual age. Children will undergo multiple measures of attention at 18 months' corrected age. The primary outcome is the average time to be distracted when attention is focused on a toy. Secondary outcomes are other aspects of attention, and (where possible) an assessment of cognition, language and motor development with the Bayley Scales of Infant and Toddler Development, Third Edition. A minimum of 72 children will be assessed to ensure 85% power to detect an effect on the primary outcome. Families, and research personnel are blinded to group assignment. All analyses will be conducted according to the intention-to-treat principal. Ethics and dissemination: All procedures were approved by the relevant institutional ethics committees prior to commencement of the study. Results will be disseminated in peer-reviewed journal publications and academic presentations. Trial registration number: ACTRN12612000503820; Pre-results .